Pembinaan Peserta Didik di Sekolah Dasar Negeri Berprestasi - Fifin Wildanah; Widiawati Widiawati; Nikmah Hayati; Singgih Ginanjar (Universitas Negeri Padang, 2023)
This study aims to describe the activities of fostering students in high achieving schools. This study used a qualitative approach with a case study research design. Data analysis went through several stages, namely data reduction, data display, and data verification. Checking the validity of the data through triangulation, checking membership, and referential adequacy. The results of the study indicate that the school's management of student development activities has been carefully planned. Coaching of students in the form of academic and non-academic coaching. Academic development is carried out through the daily learning activities of students at school. Non-academic coaching in the form of extracurricular activities and strengthening the character of students through habituation both incidental, routine and programmed activities. There are student regeneration activities and coaching students to take part in academic and non-academic competitions. To measure the success of student coaching activities, an evaluation of both academic and non-academic coaching is carried out. Follow-up carried out to increase the quality of student development activities. The results of coaching are in the form of positive character, attitude or behavior as well as the academic and non-academic achievements of students.